Clinical researchChanges in plasma susceptibility to lipid peroxidation and vitamin C in preterm and full-term neonates - Agil, Ahmad; Fraile, Rafael; Acuňa-Castroviejo, Darío (Archives of Medical Science, 2008)
Introduction: This study was designed to compare the plasma lipid peroxidation (LPO) levels in preterm and full-term neonates and their respective mothers, to assess their relationship with the degree of oxidative stress and the levels of vitamin C, an important antioxidant of the body. Material and methods: The studied groups included 70 neonates, 30 preterm (24-36 weeks of gestation) and 40 full-term (37-42 weeks) neonates. Blood samples were obtained from the cord blood in neonates and from the antecubital vein in their mothers at the time of delivery. Plasma susceptibility to LPO was fluorometrically measured before and after its incubation with 2,2\'-azobis-2-amidinopropane hydrochloride (AAPH). Plasma vitamin C level was measured by HPLC. Results: The basal LPO levels were similar in all groups of patients. After AAPH incubation, however, plasma LPO significantly (P<0.0001) increased in all groups, although maternal plasma (full-term, 6.62±0.14 and preterm, 8.76±0.03 mmol/l) showed higher (P<0.001) levels of LPO than their respective babies (full-term, 5.11±0.03 and preterm, 7.74±0.15 mmol/l). AAPH-induced LPO was higher in both maternal and preterm neonates’ plasma than in full-term ones (P<0.001). Vitamin C levels were similar in maternal plasma of both groups, but preterm neonates showed higher levels than full-term ones (171.65±9.38 vs. 118.25±2.75 mmol/l respectively, P<0.001). Conclusions: The results suggest that the preterm group was more prone to LPO than the full-term group, whereas vitamin C was not correlated with the degree of oxidative stress.